2023
DOI: 10.1088/1741-2552/acb73b
|View full text |Cite
|
Sign up to set email alerts
|

EEG changes during passive movements improve the motor imagery feature extraction in BCIs-based sensory feedback calibration

Abstract: Objective. This work proposes a method for two calibration schemes based on sensory feedback to extract reliable motor imagery (MI) features, and provide classification outputs more correlated to the user's intention. Method. After filtering the raw EEG, a two-step method for spatial feature extraction by using the Riemannian Covariance Matrices (RCM) method and Common Spatial Patterns (CSP) is proposed here. It uses electroencephalogram (EEG) data from trials providing feedback, in an intermediate step com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…This approach tested in a total of 12 sessions each one of 19 min in length, undoubtedly may be attractive for clinical practice, as it contributes optimizing therapies addressed to physically provide gait training by a robotic system, and also neurofeedback or BCI training. In our approach, gait MI and passive gait training are combined in Lokomat®, which agree with some studies suggesting that the combination of MI with passive movements may be attractive for upper limb or lower limb rehabilitation of individuals with severe motor impairments [29], [30]. In fact, Delisle et al, [30] observed that better lower-limb motor imagery features can be extracted using as a reference EEG changes from passive movements.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This approach tested in a total of 12 sessions each one of 19 min in length, undoubtedly may be attractive for clinical practice, as it contributes optimizing therapies addressed to physically provide gait training by a robotic system, and also neurofeedback or BCI training. In our approach, gait MI and passive gait training are combined in Lokomat®, which agree with some studies suggesting that the combination of MI with passive movements may be attractive for upper limb or lower limb rehabilitation of individuals with severe motor impairments [29], [30]. In fact, Delisle et al, [30] observed that better lower-limb motor imagery features can be extracted using as a reference EEG changes from passive movements.…”
Section: Discussionsupporting
confidence: 82%
“…In our approach, gait MI and passive gait training are combined in Lokomat®, which agree with some studies suggesting that the combination of MI with passive movements may be attractive for upper limb or lower limb rehabilitation of individuals with severe motor impairments [29], [30]. In fact, Delisle et al, [30] observed that better lower-limb motor imagery features can be extracted using as a reference EEG changes from passive movements. Therefore, similar brain regions around the foot area (Cz) may be activated when an individuals received gait passive training in Lokomat®.…”
Section: Discussionsupporting
confidence: 82%
“…However, some related studies can be mentioned. For example, some studies have reported the use of CSP-based methods to classify upper-and lower-limb MI tasks, where Accs close to 0.75 have been achieved [23,36]. However, little is known about these algorithmic strategies in pedaling AM tasks, where it is possible to highlight that, in our study, it was possible to obtain an Acc close to 0.81.…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, our findings make a contribution to the neuroscience community where we observed that pedaling tasks can be detected using EEG and machine learning-based techniques. Recently, our team has been interested in the study of neuroscience and BCIs with promising applicators to lower limbs rehabilitation using MMEBs [5,18,28,36]. However, one of the limitations identified from this work was that a real-time BCI was not implemented to classify pedaling tasks with an end-effector, which may limit the scope of our results.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed method integrates cutting-edge technologies including tDCS, MI-BCI, VR, and a customized MP to facilitate the lower-limb rehabilitation of post-stroke patients. This innovative system also introduces a novel approach to BCI calibration, combining EEG signals from both MI and actual movements [19], fostering a real-time closed-loop system for neural rehabilitation. Furthermore, the study highlights the potential benefits and cost-effectiveness of tDCS in inducing cortical plasticity for motor recovery in lower-limb rehabilitation, aiming to mitigate neuromuscular disabilities and associated societal costs.…”
Section: Introductionmentioning
confidence: 99%